The Effect of Brand Image and Product Quality on Purchase Decision Through Purchase Intention at The Investment Gallery of Universitas Sarjanawiyata Tamansiswa - Lusia Tria Hatmanti Hutami; Lalu Supardin; Enggar Kartika Cahyaning; Bernadetta Diansepti Maharani; Nico Pratama (PT SOLUSI EDUKASI BERDIKARI, 2024)
Investing is an important activity to achieve financial stability and personal economic growth. The investment gallery is an investment option that is increasingly popular among the public. This research aims to investigate people's perceptions and views on investing and the factors that influence it. The research method used is survey and quantitative data analysis. Samples were taken from various levels of society using a questionnaire as a data collection instrument. This research aims to analyze the influence of brand image and product quality on purchase decisions through purchase intention at the investment gallery at Universitas Sarjanawiyata Tamansiswa. This research provides an important contribution to the development of marketing strategies investment gallery in the academic environment.